Effect of cover crop use on a continuous soybean sequence in the pampean semiarid region (Semiárida, 2020)
The objectives were to quantify its effect on the yield of the successor summer crop, to evaluate the dynamics of the decomposition of rye residues from a fertilized and unfertilized cover crop (CC), and to evaluate the cumulative effect of 5 years of rye CC in a rotation with a high incidence of soybean on the soil organic matter contents. The study was carried out on a petrocalcic Paleustoll, located in the Southern Plain of the Semiarid Pampa Region. The experiment was part of a long term trial where in 2010 two treatments for soybean management were installed, continuous soybean without CC and soybeans in rotation with CC. In 2018 an experimental design was established where plots were arranged in completely randomized blocks and 4 management treatments for soybean cultivation were established: continuous soybean without CC, soybean in rotation with CC without fertilization, fertilized with 60 kg N.ha-1, and with 120 kg N.ha-1. Nitrogen fertilization in the CC improved the capture rate of both carbon, nitrogen and phosphorus. The results showed that 40% carbon, 60% nitrogen, and 61% phosphorus contained in aboveground biomass were lost from the CC from drying to soybean harvest. The highest soybean yields were recorded in the rotation with fertilized CC, due to a positive effect between the higher soil water content in the early stages of cultivation due to a greater amount of residues, and also by the contribution of different nutrients during the soybean crop cycle.  The long term trial showed that after 5 years of cover crops in the soybean rotation there was no effect on the organic matter contents.
Keywords: water content; cover crops decomposition; organic matter;